Becoming Earth - Saulitis, Eva, 1963-2016 (Book collections on Project MUSE., 2016)
"How strange that a cancer story is a story of earth, of being a creature on earth--this particular, damaged earth, at this time--a thing of nature, responding to natural laws, like any wild being, be it river or sparrow or cloud. How strange to occupy a mortal body for what is, in the end, a very short time, in total denial of death. It took two years of living with metastatic cancer to recognize there is no difference, to recognize that living is not separate from dying. It is not yet time to dig a grave, but time to wander the woods, seeking a good site. It is time to gather all I love most around me. It is a time, as always throughout my life, to write. An accurate journal of today would be similar to the burned journals of thirty years ago--nature as a steadying force in the path of a stumbling soul. You think you're making a soul, when it's not that simple. It's being made, and you're only partly the maker. This is not fighting cancer, but fighting for dignity and purpose in the face of it. An atheist to the end, to my mind this is nevertheless enacting spirit, what is beyond the body's story. The body's questions, like languages, originate in the earth; they return to the earth"--Provided by publisher.